Numerical Analysis of a Fractional Order Discrete Prey â€“ Predator System with Functional Response - George Maria Selvam, A.; Janagaraj, R. (International Journal of Engineering and Technology, 2018)
This study presents numerical examples of Discrete Fractional Order Prey Predator interactions with Functional Response. The process of discretization is applied and the version of discrete equations is obtained. Fixed points are determined and the stability around the fixed points is analyzed. Also the theoretical analysis has been verified from the numerical simulations, which help better understanding of the proposed system. Rich dynamics of system is exhibited by Bifurcation diagram and Periodic Oscillations for suitable parameters values.Â Â